Effects of PCSK9 inhibitors on metabolic-associated fatty liver disease: a short review - Ewelina Jakielska; Paweł Głuszak; Marta Walczak; Wiesław Bryl (Gastroenterology Review)
Metabolic-associated fatty liver disease (MAFLD), previously known as non-alcoholic fatty liver disease, is a significant epidemiological problem and a well-known cardiovascular risk factor. The increasing number of cases creates the need for new therapeutic methods aimed at improving patient outcomes. Recent studies have highlighted the relationship between MAFLD and proprotein convertase subtilisin/kexin type 9 (PCSK9). Based on the available data, PCSK9 inhibitors appear to have beneficial effects in patients with MAFLD, and they may be a treatment option in the future. Further research is necessary to better evaluate the efficiency of PCSK9 inhibitors in MAFLD treatment.